A. 1
B. 2
C. 3
D. 4
C
\(\mathop {\lim }\limits_{x \to {1^ - }} y = \mathop {\lim }\limits_{x \to {1^ - }} \frac{{4x - 3}}{{2{x^2} - x - 1}} = - \infty ;\)
\(\mathop {\lim }\limits_{x \to {1^ + }} y = \mathop {\lim }\limits_{x \to {1^ + }} \frac{{4x - 3}}{{2{x^2} - x - 1}} = + \infty \)
\(\mathop {\lim }\limits_{x \to {{\frac{1}{2}}^ - }} y = \mathop {\lim }\limits_{x \to {{\frac{1}{2}}^ - }} \frac{{4x - 3}}{{2{x^2} - x - 1}} = + \infty ;\)
\(\mathop {\lim }\limits_{x \to {{\frac{1}{2}}^ + }} y = \mathop {\lim }\limits_{x \to {{\frac{1}{2}}^ + }} \frac{{4x - 3}}{{2{x^2} - x - 1}} = - \infty\)
Suy ra x = 1 và là hai tiệm cận đứng của đồ thị hàm số.
\(\mathop {\lim }\limits_{x \to + \infty } y = \mathop {\lim }\limits_{x \to + \infty } \frac{{\frac{4}{x} - \frac{3}{{{x^2}}}}}{{2 - \frac{1}{x} - \frac{1}{{{x^2}}}}} = 0;\)
\(\mathop {\lim }\limits_{x \to - \infty } y = \mathop {\lim }\limits_{x \to - \infty } \frac{{\frac{4}{x} - \frac{3}{{{x^2}}}}}{{2 - \frac{1}{x} - \frac{1}{{{x^2}}}}} = 0\)
là tiệm cận ngang của đồ thị hàm số.
Câu hỏi trên thuộc đề trắc nghiệm dưới đây !
Copyright © 2021 HOCTAP247